Application of Vacuum Ultraviolet Lamp-based Photoionization Mass Spectrometry in the Monitoring of Catalytic Reaction Processes - WU Chen-xin; HUA Lei; CHEN Ping; JIANG Ji-chun; LI Jin-xu; LI Hai-yang (Zhipu Xuebao, 2024)
The study of catalytic reaction mechanism is a critical and extremely challenging project. Online monitoring of reactants, intermediates and products during catalytic reactions can provide key evidence for the in-depth study of complex catalytic reaction networks, reaction pathways and reaction kinetics. As an online mass spectrometry based on soft ionization technique, vacuum ultraviolet photoionization mass spectrometry (VUV-PIMS) has proven itself as a versatile and powerful analytical technique for online and real-time process monitoring, which has gradually become a highly concerned characterization technique for catalytic reaction processes due to its advantages of high molecular ion yield, simple spectrum interpretation and high sensitivity. Compared with other commonly used synchrotron radiation and laser-based VUV light sources, the low pressure discharge lamps filled with various rare gases are compact, easy to operate, and low cost, such as krypton discharge lamps. However, the relatively low photon intensity of these lamps limits their applications. The efforts have been taken to develop stronger VUV light sources or lamp-based efficient combined ion sources to solve this issue. In this paper, the development of VUV-PIMS technology, especially the research progress of photoionization ion sources based on the VUV lamp, were reviewed, such as high-pressure photoionization (HPPI) source, single photon ionization-photoelectron ionization (SPI-PEI) combined ion source, and single photon ionization-chemical ionization (SPI-CI) combined ion source. By combining capillary sampling technology or molecular beam sampling technology, the applications of VUV-PIMS for real-time and online monitoring of stable products and active intermediates in catalytic processes were introduced, such as ammonia synthesis, methane/ethane catalytic conversion, methanol to olefins. The applications in online monitoring of these catalytic reaction processes exhibited an excellent performance and wide potential applications of VUV-PIMS in process monitoring and reaction mechanism research. Finally, the future development trend of VUV-PIMS was prospected for the application requirements of accurate characterization of catalytic reaction process.